Are We Overestimating Demand for Microloans? - Anand, Malika; Rosenberg, Richard (World Bank, Washington, DC, 2012)
This brief addresses demand for micro credit only, not demand for microfinance or other microfinance services, such as savings or funds transfers, which may be greater than the demand for micro credit. For instance, the ratio of savers to borrowers is about 10-to-1 for Bank Rakyat Indonesia, 9-to-1 for Centenary Bank in Uganda, and 4-to-1 for PRODEM in Bolivia (MIX Market). Micro credit demand estimates address the amount of funding required: the expected number of active borrowers is multiplied by an assumed average outstanding loan amount. Reasonable estimates of average loan size can be derived from international databases maintained by the mix market and micro credit summit. But estimating numbers of expected borrowers can be a minefield. This brief discusses the kinds of reductions that should be factored into a demand estimate and looks at some all too-sketchy empirical evidence about the size of those reductions. Most-but not all-of this evidence raises a concern that demand may often be overestimated by a considerable margin.